1997
DOI: 10.3109/00365529709025098
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 7-36 Amide and Peptide YY Have Additive Inhibitory Effect on Gastric Acid Secretion in Man

Abstract: The present study suggests that the interaction between GLP-1 and PYY in man is of the additive type. The results indicate that GLP-1 and PYY have an important role in the physiologic control of gastric acid secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 23 publications
0
28
2
2
Order By: Relevance
“…Interestingly, our previous study showed that peptide YY (PYY), another gut hormone also produced by intestinal L cells in response to nutrient digestion, stimulated intestinal apo A-IV synthesis without a change in apo A-IV mRNA level (27). GLP-1 and PYY share several functions, such as inhibition of gastric acid secretion (46), upper GI motility (2,30), and food intake (6,21). However, they also have some differences.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, our previous study showed that peptide YY (PYY), another gut hormone also produced by intestinal L cells in response to nutrient digestion, stimulated intestinal apo A-IV synthesis without a change in apo A-IV mRNA level (27). GLP-1 and PYY share several functions, such as inhibition of gastric acid secretion (46), upper GI motility (2,30), and food intake (6,21). However, they also have some differences.…”
Section: Discussionmentioning
confidence: 96%
“…The effect on pancreatic exocrine secretion was first suspected to be secondary to the inhibition of gastric emptying, but in subsequent studies, GLP-1 was demonstrated to also inhibit pancreatic secretion in response to intraduodenal stimulation (84). The inhibitory effect of GLP-1 on acid secretion could be elicited by physiological elevations of the GLP-1 concentrations in plasma and was, remarkably, additive to the inhibitory effects of PYY, which is released from the L-cell in parallel with GLP-1 (324). Together the two peptides almost abolished gastrin-stimulated secretion, indicating that these two peptides are the likely mediators of the "ileal brake effect," i.e., the endocrine inhibition of upper gastrointestinal functions elicited by the presence of unabsorbed nutrients in the ileum (113,163,249).…”
Section: E Effects On the Gastrointestinal Tractmentioning
confidence: 99%
“…In human, GLP-1 and PYY are potent inhibitors on sham feeding-induced gastric acid secretion [88]. The additive type of inhibition by postprandial levels of GLP-1 and PYY was also observed with pentagastrin-stimulated gastric acid secretion in human volunteers [87].…”
Section: Pyy Is a Potent Inhibitor Of Gastric Acid Secretionmentioning
confidence: 95%